Introduction to Multiphase Flow Basic Concepts, Applications and Modelling - Yadigaroglu, George; Hewitt, Geoffrey F.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book is the maiden volume in a new series devoted to lectures delivered through the annual seminars "Short Courses on Multiphase Flow," held primarily at ETH Zurich continuously since 1984. The Zurich short courses, presented by prominent specialists in the various topics covered, have attracted a very large number of participants. This series presents fully updated and when necessary re-grouped lectures in a number of topical volumes. The collection aims at giving a condensed, critical and up-to-date view of basic knowledge on multiphase flows in relation to systems and phenomena encountered in industrial applications. The present volume covers the background of Multiphase Flows (MPF) that introduces the reader to the particular nature and complexity of multiphase flows and to basic but critical aspects of MPFs including concepts and the definition of the quantities of interest, an introduction to modelling strategies for MPFs, flow regimes, flow regime maps and transition criteria. It also deals with the ubiquitous needs of the multiphase-flow modeller, namely pressure drop and phase distribution, i.e., the void fraction and the topology of the phases that determines the flow regimes. .
Nature of Multiphase Flows and Basic Concepts -- Modelling Strategies and Two-Phase Flow Models -- Interfacial Instabilities -- Flow Regimes -- Void Fraction - Empirical Methods -- Pressure Drop - Empirical Methods -- Appendix I: Tutorial -- Appendix II: Common Nomenclature -- Appendix III: Most Common Conversion Factors.
Keywords: Fluid mechanics; Condensed matter; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Chemistry, Technical; Engineering Fluid Dynamics; Phase Transitions and Multiphase Systems; Engineering Thermodynamics, Heat and Mass Transfer; Industrial Chemistry